Digital government excellence lessons from effective digital leaders - Sikkut, Siim (Wiley, 2022)
Digital Government Excellence: Lessons from Effective Digital Leaders delivers a fascinating treatment of digital leadership as governments around the world start or restart the digital transformation of their work and service delivery.